The hemoglobin glycation index stratifies heart failure phenotypes and in-hospital risk - Lyu, Chuxin; Tong, Xinyu; Fu, Pingyang; Gao, Yuan; Hua, Jiayi; Zhao, Jiajing; Yu, Peng; Chen, Xiaohu; Lyu, Dongling (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the association between the hemoglobin glycation index (HGI) and ejection fraction (EF) categories in hospitalized heart failure (HF) patients and to investigate the relationship between HGI and in-hospital worsening heart failure (WHF).MethodsThis single-center retrospective study included 647 HF patients (261 HFrEF, 186 HFmrEF, 200 HFpEF). HGI was calculated as measured HbA1c minus predicted HbA1c (derived from fasting plasma glucose regression). Ordinal multinomial logistic regression and binomial logistic regression were used to evaluate the relationships between HGI (exposure) and EF-based phenotypes and in-hospital WHF (outcome), respectively, with stepwise adjustment for confounding factors. Dose-response relationships were assessed using restricted cubic spline (RCS) analysis.ResultsHFrEF patients exhibited the highest HGIs and the highest incidence of In-hospital WHF (33.72% vs. 18.82% [HFmrEF] and 14.00% [HFpEF]; P < 0.001). After full adjustment, a higher HGI was significantly associated with the HFrEF phenotype. For every 1-unit increase in HGI, the probability of being classified into a higher EF category (HFrEF → HFmrEF/HFpEF) decreased by approximately 25% (OR = 0.746, 95% CI 0.617–0.902; P = 0.003; P for trend = 0.029). Regarding outcomes, HGI showed a stable, positive association with In-hospital WHF. After full adjustment, every 1-unit increase in HGI increased the risk of In-hospital WHF 2.16-fold (OR = 2.161, 95% CI 1.680–2.840; P<0.001). When divided into quartiles (Q1 as reference), the ORs for In-hospital WHF in Q2, Q3, and Q4 were 2.790, 3.811, and 7.322, respectively (P for trend < 0.001). RCS analysis revealed an approximately linear dose–response relationship.ConclusionIn hospitalized HF patients, a higher HGI was significantly associated with the HFrEF phenotype and an increased risk of in-hospital WHF. HGI may serve as a potential supplementary indicator for phenotype characterization and risk stratification.